Contribution to the taxonomy and nomenclature of Entiminae from the Palearctic region and South Africa (Coleoptera: Curculionidae). - Yunakov, Nikolai Nikolaevich; Klass, Klaus-Dieter (Beiträge zur Entomologie = Contributions to Entomology, 2012)
Synonymie wird für die folgenden Taxonnamen neu etabliert: Ellimenistes Boheman, 1843 = Pimelorrhinus Reitter, 1915, syn. n.; Ellimenistes setulosus Fåhraeus, 1871 = Pimelorrhinus globatus Reitter, 1915, syn. n.; Polydrusus subgen. Eudipnus C. G. Thomson, 1859 = Eudipnoidius Apfelbeck, 1898 syn. n.; Polydrusus subgen. Eustolus C. G. Thomson, 1859 = Tylodrusinus Reitter, 1916, syn. n.; Polydrusus impar Gozis, 1882 = P. impar vranicensis Reitter, 1905, syn. n.; Chiloneus Schoenherr, 1842 = Chilonorrhinus Reitter, 1915, syn. n.; Wittmerella Pesarini, 1973 = Sciaphilomorphus Alonso-Zarazaga & Lyal, 1999 syn. n. Neue Kombinationen werden vorgeschlagen: Otiorhynchus (Eunihus) pisidicus (Magnano, 2001) comb. n. aus Parameira Seidlitz, 1868; Ellimenistes globatus Reitter, 1915, comb. n. aus Pimelorrhinus Reitter; Chiloneus sitonoides (Reitter, 1915), comb. n., Chiloneus corcyreus (Penecke, 1935), comb. n., Chiloneus aliquoi (Pesarini, 1974), comb. n., und Chiloneus sahlbergi (Reitter, 1915), comb. n. aus Chilonorrhinus Reitter; Wittmerella aurosa (Boheman, 1845) comb. n. und W. sulcirostris (Chevrolat, 1860) comb. n. aus Sciaphilomorphus Alonso-Zarazaga & Lyal. Designierung von Typusarten: für Chilonorrhinus Reitter, 1915: 187 (= Chiloneus Schoenherr) – Chilonorrhinus sitonoides Reitter, 1915. Stichwörter Curculionidae, Entiminae, new synonym, new combination. Nomenklatorische Handlungen iris Fabricius, 1792 (Curculio), LT now a synonym of Polydrusus cervinus (Linnaeus, 1758) Chilonorrhinus Reitter, 1915 (Entiminae), syn. nov. of Chiloneus Schoenherr, 1842 Eudipnoidius Apfelbeck, 1898 (Entiminae), syn. nov. of Eudipnus C.G.Thomson, 1859, subgenus of Polydrusus Germar, 1817 Sciaphilomorphus Alonso-Zarazaga & Lyal, 1999 (Entiminae), syn. nov. of Wittmerella Paserini, 1973 Tylodrusinus Reitter, 1916 (Entiminae), syn. nov. of Eustolus C.G.Thomson, 1859, subgenus of Polydrusus Germar, 1817 pisidicus (Magnano, 2003) (Otiorhynchus (Eunihus)), comb. nov. hitherto Parameira pisidicus Magnano, 2003 volgense Korotyaev, 1992 (Parameira), syn. nov. of Parameira (Lepidostomodes) gebleri Faust, 1893 globatus Reitter, 1915 (Pimelorrhinus), syn. nov. of Ellimenistis setulosus Fahraeus, 1871 Synaptorhinus Faust, 1889 (Polydrusini), replacement hitherto in Brachyderini or Sciaphilini vranicensis (var. of impar) Reitter, 1905 (Polydrusus), syn. nov. of Polydrusus (Metallites) impar Gozis, 1882 julianus Reitter, 1916 (Polydrusus (Eustolus)), LT described as Polydrusus julianus Reitter, 1916 simplex Faust, 1889 (Synaptorhinus), LT